Data Integration Case Study for UUM ASIS Student's Marks - Al-Badareen, Anas Bassam (2008)
The primary purpose of this study is to migrate data from Microsoft Excel Sheets to ASIS UUM Portal System. In UUM, lecturers normally move data from Microsoft Excel Sheets to ASIS UUM Portal system using manual methods. The traditional method of migrating data from Microsoft Excel to Database has many problems which include inaccuracy, time wastage and inefficiency. This project is aimed at development middleware system that will migrate data from Microsoft Excel to ASIS UUM Portal system effectively and accurately.